2016
DOI: 10.1016/j.ajog.2016.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on vaginal health in pregnancy. EFFPRO, a randomized controlled trial

Abstract: Oral probiotics may be suitable for implementation in antenatal care but, as administered here, had no effect on vaginal health during mid gestation. Other application routes or probiotic preparations may be more effective in supporting vaginal microbiota during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 33 publications
3
40
0
4
Order By: Relevance
“…BV is an inflammatory vaginal disease caused by a disturbance of the vaginal microbiota, including a decrease in the number of beneficial bacteria, such as lactobacilli, and an increase in the number of harmful bacteria, such as GV and AV [4,10,21]. BV increases the risk of infection by sexually transmitted pathogens, such as HIV-1, and carries a risk of early delivery in pregnant women [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BV is an inflammatory vaginal disease caused by a disturbance of the vaginal microbiota, including a decrease in the number of beneficial bacteria, such as lactobacilli, and an increase in the number of harmful bacteria, such as GV and AV [4,10,21]. BV increases the risk of infection by sexually transmitted pathogens, such as HIV-1, and carries a risk of early delivery in pregnant women [22].…”
Section: Discussionmentioning
confidence: 99%
“…Although antibacterial drugs, such as clindamycin and metronidazole, are commonly used for BV treatment, probiotics are frequently recommended due to infection recurrence and drug resistance [7,8]. Unlike anti-bacterial drugs, microbiota-friendly probiotics may attenuate vaginosis by killing or out competing pathogens in the vagina [9,10,23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study in Norway demonstrated an association between high intake of probiotic dairy products and reduced risk of spontaneous preterm delivery (Table 2) [30]. A more recent study showed no significant difference in the vaginal microbiota after eight weeks of probiotics, starting at the end of the first trimester [31]; however, the incidence of bacterial vaginosis was low (2.8%) in the treatment group.…”
Section: Probiotic Administration In Pregnancymentioning
confidence: 99%
“…Evidence suggests that restoration of the vaginal microbiota and/or modulation of the local mucosal immune response can be achieved via supplementation with probiotics, which can be administered orally as a probiotic food supplement, intra-vaginally as vaginal suppositories, or applied topically as a gel (Gille et al 2016;Stapleton et al 2011;Zeng et al 2010). Bertuccini et al (2017) evaluated the effects of L. rhamnosus HN001 and L. acidophilus GLA-14 on bacterial vaginal pathogens (G. vaginalis and A. vaginae) and aerobic vaginitis (AV) (S. aureus and E. coli).…”
Section: Probiotics and Prebiotics On The Health Of The Female Urogenmentioning
confidence: 99%